Visual analysis of the finite‐time lyapunov exponent - Sagristà Sellés, Antoni; Jordan, Stefan; Sadlo, Filip (Computer graphics forum, 2020)
In this paper, we present an integrated visual analytics approach to support the parametrization and exploration of flow visualization based on the finite‐time Lyapunov exponent.
Gesehen am 14.09.2020